Consecuencias de una relación entre una menor de edad y una persona privada de libertar de un centro de reclusión - Sanchez Bonilla, Joselin Viviana (2021)
The purpose of this case study is to determine the consequences generated by being confined in a social rehabilitation center for rape of a minor in the city of Guaranda, Bolivar province. The consequences of the love relationship of a ppl with of a minor play a very important role in the psychological area since they tend to see adverse situations that arise on a day-to-day basis. For the collection of patient information, instruments such as: the semi-structured interview, tools (clinical history, observation and application of psychometric test) were used specifically to evaluate the PHT and as a complement a questionnaire that defines the personality of the individual, which allowed carry out an adequate psychological assessment and determine the consequences that have generated the deprivation of liberty for rape.